2004
DOI: 10.1016/j.icesjms.2003.12.007
|View full text |Cite
|
Sign up to set email alerts
|

Risk and strategy of fishers alternatively exploiting sea bream and tuna in the Gibraltar Strait from an efficiency perspective

Abstract: Herrero, I. 2004. Risk and strategy of fishers alternatively exploiting sea bream and tuna in the Gibraltar Strait from an efficiency perspective. e ICES Journal of Marine Science, 61: 211e217.While in the last few years interest in efficiency analyses has increased among fisheries economists, efficiency analyses have not been used so far to compare the profitability of alternative fisheries. We compared the profitability of the sea bream fishery and the tuna fishery, both operating in the South of Spain (Gibr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0
2

Year Published

2005
2005
2019
2019

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 19 publications
0
3
0
2
Order By: Relevance
“…The results also show that full participation in development-oriented FIPs remains dependent on the characteristics of the individual fishing firm. The results indicate that fishers fully participating in PPTST FIP have a greater degree of operation, for instance by their large capacity to finance high costs of operation at a farther distance and through their capability to cope with risks associated with full-time tuna fishing particularly from March to September where catches are lower (see for example [ 68 ]). However, partial participation is dominated by those fishers with smaller ‘one-man, one-boat’ operations, characterised by fishing at shorter distance from shore, and who are dependent on collective capabilities supported by fishing associations and Casas (see [ 69 ] for comparable results).…”
Section: Discussionmentioning
confidence: 99%
“…The results also show that full participation in development-oriented FIPs remains dependent on the characteristics of the individual fishing firm. The results indicate that fishers fully participating in PPTST FIP have a greater degree of operation, for instance by their large capacity to finance high costs of operation at a farther distance and through their capability to cope with risks associated with full-time tuna fishing particularly from March to September where catches are lower (see for example [ 68 ]). However, partial participation is dominated by those fishers with smaller ‘one-man, one-boat’ operations, characterised by fishing at shorter distance from shore, and who are dependent on collective capabilities supported by fishing associations and Casas (see [ 69 ] for comparable results).…”
Section: Discussionmentioning
confidence: 99%
“…We used the Charnes et al (1981) technique to compare efficiency both within the groups of firms and also between them. While this is a very useful method and has been used in a few economics studies (Herrero, 2004;Pascoe & Herrero, 2004), it has never been used in the area of human resources. When the purpose of a study lies in comparing the performance of two groups, Charnes et al (1981) suggested eliminating the efficiency component before comparing the efficient frontier of each of the two groups.…”
Section: T a B L E V I I I Organizational Capabilities In Sectorsmentioning
confidence: 99%
“…Although, striped red mullet has a lower income price than bogue. This practice may prove that different fishing strategies and fishermen preferred this métier, which presents a lower risk [45]. Métier Gill2 used gillnet, presenting, as a result, higher gross cash flow, even though B. boops has a low market price.…”
Section: Discussionmentioning
confidence: 95%